(untitled) (Jurnal Al-Fikrah, 2023)
This study focuses on a current social reality, where there is a crisis in the privacy space of social media users on various social media platforms. On the one hand, various social media platforms already offer a "private account" feature, but on the other hand, social media users cannot control the content they upload on social media, even though the private account feature has been activated. Social media opens up freedom to upload whatever they want, but uploaders do not have full control over their uploads, so they can be accessed by other social media users at any time. This phenomenon is an anomaly in the privacy space in network society. The study of the privacy crisis will be seen from the perspective of the Al-Qur’an, Surah Al-Hujarat Verses 11-12. The aim of this study is to analyze the interpretation of the Al-Qur’an Surah Al-Hujarat Verses 11-12 regarding the phenomenon of anomalous space in network society. This research uses qualitative research, which is descriptive analysis, with a type of document analysis research (content analysis), so this research is included in library research. The tafsir books that are references are the book Tafsir Hasyiyah Al-Shawi ’Ala Tafsir Jalalain and the book Tafsir Al-Misbah. The results of the study showed that the two verses of Surah Al-Hujarat really respect the realm of human privacy. The contents of these two verses include prohibitions that could potentially disturb or intrude on someone’s privacy. These two verses can be said to be an early warning of the dangers or impacts that will occur if someone’s privacy is violated, namely that there will be disputes, disputes, even hostility.